Better than okay : finding hope and healing after your marriage ends - Wilson, Brandi (Bethany House, a division of Baker Publishing Group, 2023)
"When her husband of 20 years left, Brandi Wilson's life and dreams shattered. Now a ministry leader and life coach, she tenderly and vulnerably shares her story, helping you confront the grief and heartache of divorce head-on. Through God's grace, you can endure the darkest seasons, grow from the pain, and find hope for renewed joy, peace, and redemption"--